The Right to Use Legal Remedies Against Court Decisions in Contested Procedure - Arbnor Ajet Ajeti (Sriwijaya Law Review, 2020)
The purpose of this scientific paper is to handle in detail the main issues concerning the right to use legal remedies by the parties against court decisions. The right to use legal remedies against court decisions is recognized as one of the fundamental rights of litigants in the civil contested procedure. Due to the importance of using legal remedies in this procedure and other court proceedings, the right to use legal remedies is also foreseen by legal acts. We emphasize this because the right to use legal remedies is guaranteed by the Universal Declaration of Human Rights of 1948, by the European Convention on Human Rights of 1950. Also, the right to use legal remedies is guaranteed through the Constitution of the Republic of Kosovo of 2008 as one of the fundamental human rights. In contrast, the procedure, according to appealing means, has been regulated by the Law on Contested Procedure of Kosovo 2008. The main idea of this scientific paper is to clarify the right of parties to use legal remedies and what are legal remedies to this procedure. The results of handling consist of understanding the importance of legal remedies, in which cases legal remedies may be submitted, and their impact in exercising the right of litigants in order to provide protection to the legal interests of the parties. In this scientific paper have been conducted handlings concerning the right to use legal remedies, types of appealing means, ordinary legal remedies, and extraordinary legal remedies. This scientific paper is based on applicable legislation, judicial practice, and legal doctrine. In this paper are also given conclusions regarding the right to use legal remedies against court decisions in the contested procedure.